Iron deficiency in patients with heart failure. Issue 1 (2nd January 2015) - Fitzsimons, Sarah; Doughty, Robert Neil
Abstract : Iron deficiency (ID) is a commonly present co-morbidity in patients with heart failure (HF). In iron deficient but otherwise healthy individuals, correction of ID restores exercise capacity and endurance regardless of the presence of anaemia. Recently, iron replacement in patients with HF with reduced ejection fraction has been shown to improve symptoms and exercise capacity. This article reviews the clinical relevance of ID in HF and evidence for iron replacement.